Students’ Perceptions of Effective Techniques for Vocabulary Learning in Senior High School - Rita Rita; Budi Budi; Andi Patmasari; Wahyudin Wahyudin (Universitas Pahlawan Tuanku Tambusai, 2026)
Learning vocabulary is crucial to being fluent in English, but students frequently struggle to select efficient teaching techniques. Many vocabulary acquisition techniques have been covered in earlier research, but little focus has been placed on how students perceive which techniques work best in their real-word learning environment. The purpose of this study was to investigate students perceived efficient techniques for learning vocabulary. The participants consisted of 29 eleventh-grade students of SMK Negeri 1 Taopa who completed a questionnaire and 5 students who participated in semi-structured interviews. The collected data were analysed using descriptive qualitative analysis. The results showed that students employed a variety of techniques for learning vocabulary, such as memory, cognitive, social and communication, game-based, and technology-based techniques. The most successful of these were found to be social and communication technique and game-based learning. These techniques were favoured because they were engaging, participatory, and improved students’ comprehension.